2009
DOI: 10.1007/s10086-009-1057-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lateral growth rate on wood properties in fast-growing hardwood species

Abstract: We investigated the feasibility of using several fast-growing tropical or subtropical hardwood species for timber production by measuring key wood qualities in relationship to the high rates of lateral growth. The trees tested were sampled from even-aged plantations of Acacia mangium, A. auriculiformis, hybrid Acacia(A.mangium × A. auriculiformis), Eucalyptus grandis, E. globulus, and Paraserianthes falcataria (Solomon and Java origin) that had already reached commercial harvesting age. The released strain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 14 publications
5
33
0
2
Order By: Relevance
“…In the present study, no significant differences were found among three categories in almost all characteristics and properties, except for vessel element length and cell wall thickness of wood fiber (Table 2). These results are similar to those obtained in Kojima's research on several fast-growing tree species (Kojima et al 2009b). Based on the results, we conclude that, in D. mollissimum, faster radial growth characteristics do not always result in the production of wood of lower quality.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics supporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, no significant differences were found among three categories in almost all characteristics and properties, except for vessel element length and cell wall thickness of wood fiber (Table 2). These results are similar to those obtained in Kojima's research on several fast-growing tree species (Kojima et al 2009b). Based on the results, we conclude that, in D. mollissimum, faster radial growth characteristics do not always result in the production of wood of lower quality.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics supporting
confidence: 90%
“…Therefore, we conclude that wood properties, including basic density and Young's modulus of D. mollissimum trees, are independent from growth characteristics. Kojima et al (2009b) examined growth stress, wood density, microfibril angle, and wood fiber length in several fast-growing tree species. They found that, with a few exceptions, these characteristics are constant, regardless of the Fig.…”
Section: Effects Of Radial Growth Rate On Anatomical Characteristics mentioning
confidence: 99%
“…Conversely crooked, twisted trunk of A. auriculiform makes it unsuitable for timber production (Kojima et al 2009). Similarly, although Acacia hybrids prove superior to the parents, they still carry inferior parental traits such as high lignin content, low wood density, short fibre, resistance to insect pests, disease resistance and problems associated with production of viable seeds and recalcitrant germination either naturally or through controlled pollination (Kijkar 1992;Wickneswari, Norwati 1993).…”
mentioning
confidence: 99%
“…For example, A. mangium is highly susceptible to heart rot disease. The conversely crooked, twisted trunk of A. auriculiform makes it unsuitable for timber production (Kojima et al 2009). Acacia hybrids although prove superior than parents still carry inferior parental traits such as high lignin content, low wood density, small fibre length and problems associated with production of viable seeds and recalcitrant germination either naturally or through controlled pollination (Kijar 1992;Wickneswari, Norwati 1992).…”
mentioning
confidence: 99%